PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN GREEN INNOVATION TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE GOVERNANCE SEBAGAI VARIABEL PEMODERASI - Andea Nurul Badriyah (2023)
This research is a quantitative study that aims to determine the effect of corporate social responsibility, green innovation as measured by green product innovation and green process innovation, also moderated by corporate governance proxied through managerial ownership. The samples in this study were taken from manufacturing and mining sector companies listed on the Indonesia Stock Exchange in the 2019-2021 period which were selected based on the purposive sampling method. The data obtained were 38 companies with a total sample of 114. The results of the test show that (1) Corporate Social Responsibility has no negative significant effect on firm value (2) Green product innovation has no significant effect on firm value, (3) Green process innovation has no significant effect on firm value, (4) Managerial ownership has no significant effect in moderating the relationship between corporate social responsibility and firm value, (5) Managerial ownership has no significant effect in moderating the relationship between green product innovation and firm value, (6) Managerial ownership has no significant effect in moderating the relationship between green product innovation and firm value. Based on the test results, it can be seen that these variables are less effective in influencing firm value, so that they can be used as further research.